Evaluation of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) for Poorly Water-Soluble Talinolol: Preparation, in vitro and in vivo Assessment - Kazi, Mohsin; Al-Swairi, Mohammed; Ahmad, Ajaz; Raish, Mohammad; Alanazi, Fars K.; Badran, Mohamed M.; Khan, Azmat Ali; Alanazi, Amer M.; Hussain, Muhammad Delwar (Frontiers in Pharmacology, 2019)
Objective The aim of this study was to investigate the in vitro and in vivo performance of self-nanoemulsifying drug delivery systems (SNEDDSs) of talinolol (TAL), a poorly water-soluble drug. Methods Self-nanoemulsifying drug delivery systems of TAL were prepared using various oils, non-ionic surfactants and/or water-soluble co-solvents and assessed visually/by droplet size measurement. Equilibrium solubility of TAL in the anhydrous and diluted SNEDDS was conducted to achieve the maximum drug loading. The in vitro dissolution experiments and human red blood cells (RBCs) toxicity test, ex vivo gut permeation studies, and bioavailability of SNEDDS in rats were studied to compare the representative formulations with marketed product Cordanum® 50 mg and raw drug. Results The results from the characterization and solubility studies showed that SNEDDS formulations were stable with lower droplet sizes and higher TAL solubility. From the dissolution studies, it was found that the developed SNEDDS provided significantly higher rate of TAL release (>97% in 2.0 h) compared to raw TAL and marketed product Cordanum®. The RBC lysis test suggested negligible toxicity of the formulation to the cells. The ex vivo permeability assessment and in vivo pharmacokinetics study of a selected SNEDDS formulation (F6) showed about four-fold increase in permeability and 1.58-fold enhanced oral bioavailability of TAL in comparison to pure drug, respectively. Conclusion Talinolol loaded SNEDDS formulations could be a potential oral pharmaceutical product with high drug-loading capacity, improved drug dissolution, increased gut permeation, reduced/no human RBC toxicity, and enhanced oral bioavailability.